FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM MEMILIH SURAT KABAR JAWA POS DI WILAYAH KOTA MAGELANG - Kurnia, Marlina Kurnia; Aprilliani, Carolina Aprilliani (Universitas Muhammadiyah Magelang, 2005)
The economy situation are getting growth rapidly, everyone have opportunity to create any goods with various types and patterns also they free to use their money to purchase any goods they want, so it can influence the companies to take the market compartment on very tight competition. This research aim to get some information about is there any relationship between news quality, news actulization, print equity, sistributon and good taste and consument behaviour either through partial and simultant, and also to know what factors that dominantly influences againts consument behaviour. Population is the subject of research entirely. The population of this research amount to 310 consument which subcriber to Jawa Pos newspaper in Magelang. The methods which used in this reseach was purposive quota sampling. The samples which used in this research amount to 100 respondent from some respondent who qualified with criteria above. The method analysis which used in this research is double regression linear method. The result of this research shows either through simultant and partial between news quality, news actuality, print out quality, distribution and readers taste againts consument behaviour. It shown that the variable of news quality have dominant influence againts consumer behaviour. There is suggested The Jawa Pos newspaper to improve and keep the quality, news actualization, print out quality, distribution and readers taste betterly to influence consument.